Inventario de la infraestructura civil de la vía colectora CatamayoMacará (E69) tramo Catamayo Gonzanamá como aporte al Observatorio de Ingeniería de Tráfico de la Universidad Técnica Particular de Loja - Jiménez Vega, Pablo Stalin (2018)
Abstract:The Observatory of Engineering of Traffic (OET) of the UTPL is constituted by an element of observation and difusión of information georeferenced of infrastructure and traffic variables corresponding to the state road network of Ecuador. The present study its porpuse is to supply to (OET) updated information and georeferenced of existing infrastucture in the road colectora Catamayo-Macará (E69) section Catamayo Gonzanamá as far as aspects such as road width of the road, hydraulic drainage works and risk areas produced by natural phenomena such as landslides, settlements, etc. Performing a data collection through a detailed inventory, managing information through Geographic Information Systems getting a detailed database as thematic maps that represent the civil infrastructure analyzed and the current state of the same. The availability of current status information civil infrastructure that is part of a road has great importance because it serves as a point reference both for decision making and for the planning of conservation projects, rehabilitation and maintenance of road network.